2014
DOI: 10.1371/journal.pone.0094500
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in a Multiethnic Healthy Control Cohort and Altered Immune Response in Vitamin D Deficient European-American Healthy Controls

Abstract: ObjectiveIn recent years, vitamin D has been shown to possess a wide range of immunomodulatory effects. Although there is extensive amount of research on vitamin D, we lack a comprehensive understanding of the prevalence of vitamin D deficiency or the mechanism by which vitamin D regulates the human immune system. This study examined the prevalence and correlates of vitamin D deficiency and the relationship between vitamin D and the immune system in healthy individuals.MethodsHealthy individuals (n = 774) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 95 publications
3
37
0
Order By: Relevance
“…In our study vitamin D was in positive correlation with CD4 -that represent helper cells - which has found to contain the significant amount of VDR [40]. Our study was in agreement with (Ritterhouse et al) [41] vitamin D regulates T-helper 1 (Th1) and dendritic cell function [42], which suggest that vitamin D support the innate and the adaptive immune system.…”
Section: Discussionsupporting
confidence: 90%
“…In our study vitamin D was in positive correlation with CD4 -that represent helper cells - which has found to contain the significant amount of VDR [40]. Our study was in agreement with (Ritterhouse et al) [41] vitamin D regulates T-helper 1 (Th1) and dendritic cell function [42], which suggest that vitamin D support the innate and the adaptive immune system.…”
Section: Discussionsupporting
confidence: 90%
“…Ritterhouse et al demonstrated among healthy controls that vitamin D deficiency was associated with autoimmunity (ANA positivity) 48 and with altered T and B cell responses, 51 consistent with low levels of 25(OH)D being a potential risk factor in the pathogenesis of SLE. Although causality remains to be determined, studies to date suggest a possible role for vitamin D in the pathogenesis of SLE.…”
Section: Influence Of Vitamin D Status On Slementioning
confidence: 85%
“…The first cohort (Cohort 1) consisted of plasma samples from healthy donors from the Oklahoma Immune Cohort [19]. This cohort is well characterized for autoantibodies and all donors chosen for this study were autoantibody negative.…”
Section: Methodsmentioning
confidence: 99%